A new tramway and the formation of emotional commuting experiences - Sandberg, Birgitta; Hurmerinta, Leila; Helminen, Ville; Leino, Henna M.; Vasankari, Tommi (Elsevier, 2025)
Sustainable urban mobility transitions require various measures that impact peoples’ everyday lives. Implementing these measures, such as transport infrastructure projects, requires public acceptance. However, there is a lack of research on how sustainable urban mobility transitions impact commuters’ emotional experiences. This study aims to understand the formation of emotional commuting experiences and to analyse the impact of the introduction of a tramway on those experiences. The findings are mainly based on qualitative data (33 interviews) but also on quantitative data on the participants’ commuting behaviour collected in a Finnish city, Tampere, which launched a new tramline a couple of months prior to data collection. The research shows a variety of triggers for negative and positive emotional commuting experiences and highlights the role of critical incidents in the formation of emotional experiences. It reveals how launching a tram in a city impacts emotional commuting experiences on many levels, even for those who do not change their main mode of commuting. It also shows the dynamics involved in emotional commuting experiences, demonstrating how emotional experiences in the construction phase may differ greatly from those after the new commuting mode has been launched. Based on the findings, we suggest that in order to guarantee public support for sustainable urban transport projects, practitioners should recognise the wide range of emotional experiences associated with commuting, even for those who do not adopt the new mode of transport, and take these experiences into account not only during the lengthy infrastructure-building phase but also during the utilisation phase.